2014
DOI: 10.1007/s11746-014-2486-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Molecular Species of TAG and DAG in Lesquerella (Physaria fendleri) Oil by HPLC and MS

Abstract: Ten diacylglycerols (DAG) and 74 triacylglycerols (TAG) in the seed oil of Physaria fendleri were recently identified by high-performance liquid chromatography (HPLC) and mass spectrometry (MS). These acylglycerols (AG) were quantified by HPLC with evaporative light scattering detector and electrospray ionization mass spectrometry of the lithium adducts of the AG in the HPLC fractions of lesquerella oil. The MS 1 ion signal intensities of molecular ions [M ? Li] ? in HPLC fractions of an HPLC peak were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 17 publications
(70 reference statements)
1
19
0
Order By: Relevance
“…Castor bean LPAAT2 shows enhanced HFA activity (Arroyo‐Caro et al ., ), which helps explain in part why castor bean TAGs accommodate HFAs at all three positions. However, unlike castor bean, positional analysis and HPLC measurement of TAG species in Physaria fendleri demonstrated that only low quantities of HFAs are present at the sn ‐2 position of TAGs (Hayes et al ., ; Lin and Chen, ), although there is some variability in other Paysonia and Physaria species, which show higher proportions of HFAs in the sn ‐2 position. These chemical analyses, together with the lack of divergence of the LPAAT2 sequence in Physaria (Figure ), suggest that Physaria LPAAT2 is unlikely to be specialized for HFA incorporation.…”
Section: Discussionmentioning
confidence: 99%
“…Castor bean LPAAT2 shows enhanced HFA activity (Arroyo‐Caro et al ., ), which helps explain in part why castor bean TAGs accommodate HFAs at all three positions. However, unlike castor bean, positional analysis and HPLC measurement of TAG species in Physaria fendleri demonstrated that only low quantities of HFAs are present at the sn ‐2 position of TAGs (Hayes et al ., ; Lin and Chen, ), although there is some variability in other Paysonia and Physaria species, which show higher proportions of HFAs in the sn ‐2 position. These chemical analyses, together with the lack of divergence of the LPAAT2 sequence in Physaria (Figure ), suggest that Physaria LPAAT2 is unlikely to be specialized for HFA incorporation.…”
Section: Discussionmentioning
confidence: 99%
“…Elongation seems more effective than hydroxylation to incorporate hydroxy FA into TAG at the sn-1/3 positions in lesquerella as the order of OH20 > diOH18 > OH18. The contents of TAG containing diOH18 and diOH20 were very low [6]. The block of elongation (from C 18 to C 20 ) may be used to increase the content of hydroxy FA, e.g., ricinoleate, at the sn-2 position of TAG in lesquerella.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported the contents (%) of all of these 74 molecular species of TAG in lesquerella oil [6]. From these contents and the ratios of regioisomers (Table 1) of the molecular species of TAG, the contents of individual FA at the sn-2 and sn-1/3 positions were estimated as shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations